ANALYSIS OF TEACHERS' DIGITAL LITERACY SKILLS IN INTEGRATING DIGITAL STORYTELLING IN ELEMENTARY SCHOOLS - Farah Abida Ryzqiyah; Ermawati Zulikhatin Nuroh (PIONIR: JURNAL PENDIDIKAN, 2025)
This study aims to describe teachers' digital literacy in the application of digital storytelling learning in fourth grade. The research approach used is qualitative with interview and observation methods. The research subjects were fourth-grade teachers at SD Muhammadiyah 1 Sidoarjo. The results showed that teachers had good digital literacy competencies, which were reflected in their mastery of functional skills, creativity, collaboration, communication, ability to find and select information, critical thinking and evaluation, cultural and social understanding, and cyber security. Teachers were able to utilize digital technology effectively and creatively in developing digital storytelling learning media that suited the needs of students. In addition, teachers apply a critical attitude in selecting information from the internet and instill ethical values, privacy, and digital security in students. In conclusion, teachers' digital literacy plays a vital role in creating innovative, safe, and meaningful digital storytelling learning, as well as supporting the development of students' critical thinking and digital awareness. Keywords: Digital literacy, Teacher Skills, Digital Storytelling